Effect of Seawater Ageing on Fracture Toughness of Stitched Glass Fiber/Epoxy Laminates for Marine Applications - Atizaz Hassan; Rafiullah Khan; Numan Khan; Muhammad Aamir; Danil Yurievich Pimenov; Khaled Giasin (Journal of Marine Science and Engineering, 2021)
Composite materials are used in various industries such as marine, aircraft, automotive, etc. In marine applications, composites are exposed to seawater, which can affect their mechanical properties due to moisture absorption. This work focuses on the durability of composite materials under the short-term effect of seawater ageing. The specimens were prepared from glass fiber/epoxy using a hand lap-up method and stitched in the z-direction with Kevlar fiber. The specimens were submerged in seawater for 24 and 35 days. A significant decrease in maximum load was found as specimen immersion time in seawater increased. The seawater ageing also affected fracture toughness with a reduction of 30% for 24 days immersion and 55% for 35 days. The ageing also caused the swelling of composites due to moisture absorption, which increased the weight of the specimens. Compared to the dry specimens, the weight of the specimen for 24 days increases to 5.2% and 7.89% for 35 days’ seawater ageing. The analysis also showed that due to seawater ageing, the de-bonding rate increased as the number of days increased.